STUDI KEMAMPUAN REPRESENTASI SISWA PADA POKOK BAHASAN HUKUM NEWTON - Mustika Wati; Saiyidah Mahtari; Ramlah Ramlah; Misbah Misbah (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2020)
This research was conducted with the aim of analyzing the representation ability of junior high school students in Banjarmasin on Newton's Law problems by giving a written test. The research method used was survey research, namely One-shot Design. The test was conducted on 102 middle school students who had learned Newton's Law material with representation. The results showed that students more easily understand the questions in verbal representations than mathematical representations, figures, and tables. This study also shows that students who have high learning outcomes obtain consistently good multi-representation scores. So learning by using multiple representations needs to be done to support the learning outcomes of physics.